A saposin-lipoprotein nanoparticle system for membrane proteins - Frauenfeld, Jens; Sonnen, Andreas; Briggs, John A. G. (Nature methods, 2016)
A saposin protein-lipid nanoparticle system stabilizes diverse, fragile membrane proteins in a lipid environment for structural and functional studies.